55th Anniversary of the Journal of the Faculty of Agronomy of the University of Zulia - Araujo-Febres, Omar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The journal of the Faculty of Agronomy of the University of Zulia was founded in 1968, more as a journal of “scientific dissemination” than as a scientific journal, and with variable periodicity. Considering the time, it was a great effort to obtain collaborations from the same faculty that had just begun to bear its first fruits. Its professors, relatively young, were starting out in research, due to the limited resources assigned to research, since there were numerous needs in the construction and consolidation of the faculty. Volume 7 covered a period from 1986 to 1990. Five years in four issues. In 1990 we assumed the commitment to direct the journal. Without much personal experience, but open to the recommendations that we seek within the university, in other faculties, and in other universities, and we imagine a concept of the modern scientific journal, a journal open to the reading public and open to researchers. from other national and foreign institutions. When I invited colleagues from other institutions to publish in our journal, they told us that this magazine belongs to the Faculty of Agronomy, and they did not understand that they were welcome. At that time, two separate events occurred that led to the success of the Faculty of Agronomy journal; The first was the creation of the Researcher Promotion Program (PPI) in 1990. And the second, the regularization of the publication of the journal and having modernized the concept applied to the edition. In 1993 the journal was awarded the “Tulio Arends” Prize as the best national scientific or technological journal. Then, works from researchers from all national institutions began to arrive, and it was consolidated in its frequency and in the number of works published. It was necessary to increase the publication to 6 issues per year to satisfy the demand for articles received. This continued from 1996 to 2000. In 2001 the journal was included in the Science Citation Index (SCI Expanded) and in Scopus, which began to give it international visibility, and with it the influx of articles from other countries. From then on, the Journal of the Faculty of Agronomy consolidated itself as one of the best scientific journals in Latin America. The effort it represents today to keep it running, up to date, maintaining high quality standards is extraordinary. The current editorial team deserves our deepest recognition for their effort and dedication. Finally, the Journal of the Faculty of Agronomy of the University of Zulia presents to its readers a supplement on the occasion of its 55th anniversary, which includes review articles of renowned Venezuelan researchers from different areas of agronomy that develop current issues.